PENERAPAN EKONOMI KREATIF DALAM RANGKA MENINGKATKAN KUNJUNGAN WISATAWAN DI DESA WIDOSARI, KABUPATEN KULONPROGO - siti yulia irani nugraha; eka nuraisah rosiana; hanna daniati; lien maulina; dede kuswandi (Bogor Hospitality Journal, 2024)
Widosari Tourism Village is one of the Tourism Villages in the Kulon Progo Regency. Most of the young population in Widosari Village are more interested in trying their luck in the city. This resulted in a lot of potential in Widosari Village that could not be maximized because of the lack of knowledge about economic opportunities in the village, a lack of understanding about the urgency of entrepreneurship and the creative economy that can improve the economy. The purpose of this study is to determine the strategy for implementing the creative economy and implementing the creative economy in increasing tourist visits. The research method in this research is descriptive qualitative research, which focuses on case studies. Data collection techniques using observation, interviews, and documentation. Data analysis technique using triangulation.